CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MINYAK GORENG BIMOLI DI CV. ANUGRAH AGUNG - Mutria Ferhaeni; Ni Putu Widiastuti; Ni Gusti Ayu Kade Ari Widuantari (Universitas Triatma Mulya, 2022)
This study aims to determine (1) the effect of brand image on purchasing decisions for Bimoli cooking oil at CV Anugrah Agung, (2) the effect of price on buying decisions for Bimoli cooking oil at CV. Anugrah Agung, (3) Influence of Brand Image and Price on Purchase Decision of Bimoli Cooking Oil at CV Anugrah Agung. This research is a descriptive analysis research using a quantitative approach.Collecting data using observation, documentation and questionnaires. The sample, in this study amounted to 80 people and used a random sample method (probability sampling). The validity test used Cronbach's Alpha. Data analysis used multiple linear regression. The results of the study found that (1) Brand Image has a positive and significant effect on purchasing decisions, the value of sig. 0.004 <α 0.005 indicates that H0 is rejected and H1 is rejected.(2) Price has a positive and significant effect on purchasing decisions, the value of Sig.t is 0.000<α 0.05 which indicates that H0 is rejected and H1 is accepted. (3) Brand Image and Price Together have a positive and significant influence on purchasing decisions.The simultaneous contribution or contribution of Brand Image and Price variables to purchasing decisions is 89.4% while 17.4% is determined by other variables not examined in this study.